Risk factors for early TB treatment interruption among newly diagnosed patients in Malaysia - Suliman, Qudsiah; Lim, Poh Ying; Md. Said, Salmiah; Tan, Kit-Aun; Mohd. Zulkefli, Nor Afiah (Nature Research, 2022)
TB treatment interruption has resulted in delayed sputum conversion, drug resistance, and a high mortality rate and a prolonged treatment course, hence leading to economic and psychosocial affliction. To date, there are limited studies investigating the physico-social risk factors for early treatment interruptions. This prospective multicenter cohort study aimed to investigate the risk factors for early treatment interruption among new pulmonary tuberculosis (TB) smear-positive patients in Selangor, Malaysia. A total of 439 participants were recruited from 39 public treatment centres, 2018–2019. Multivariate Cox proportional hazard analyses were performed to analyse the risk factors for early treatment interruption. Of 439 participants, 104 (23.7%) had early treatment interruption, with 67.3% of early treatment interruption occurring in the first month of treatment. Being a current smoker and having a history of hospitalization, internalized stigma, low TB symptoms score, and waiting time spent at Directly Observed Treatment, Short-course centre were risk factors for early treatment interruption. An appropriate treatment adherence strategy is suggested to prioritize the high-risk group with high early treatment interruption. Efforts to quit smoking cessation programs and to promote stigma reduction interventions are crucial to reduce the probability of early treatment interruption.